ANALISIS PEMIKIRAN KH. AHMAD IZZUDDIN TENTANG GERHANA PERSPEKTIF ILMU FALAK - Nurfaindah; Irfan; Amiruddin (Universitas Islam Negeri Alauddin Makassar, 2022)
Abstract Many people think that the occurrence of solar eclipses and lunar eclipses is an ordinary natural phenomenon, but for those who feel subservient to the majesty of the Creator, Allah swt. consider the eclipse to be an important event that clearly shows that there is a supreme power beyond human capabilities. Eclipse is an astronomical phenomenon that occurs when a celestial body covers another celestial body, a lunar eclipse occurs because part or all of the moon's cross section is covered by the Earth's shadow. Meanwhile, a solar eclipse occurs because the position of the moon is between the earth and the sun so that it covers part or all of the rays from the sun, in the event of an eclipse according to KH. Ahmad Izzuddin, namely the estimation of when the eclipse will occur can be taken from one of the books, al-Qawaid al-Falakiyah by Shaykh Abdul Fatah al-Thuty, the sun and the moon by reckoning ustadz A. Kasir and Nurul Anwar by KH. Ahmad SS, this study aims to determine the thinking method used by KH. Ahmad Izzuddin in understanding eclipses and to know the analysis of KH. Ahmad Izzuddin about eclipses in the view of astronomy, this type of research is descriptive qualitative literature (library research) research which is a series of activities related to the methods of collecting library data, reading and taking notes and changing research materials, so that researchers gain a clear understanding. And the research approach used by the researcher is the syar'i and science approach. The data sources that researchers use are primary data and secondary data. Keywords: Eclipse, Astronomy, KH. Ahmad Izzuddin